تقييم الفعالية التثبيطية لمستخلصات أشنة Evernia prunastri تجاه أنواع ممرضة للإنسان من جنس Aspergillus sp. (Latakia University Journal -Biological Sciences Series, 2017)
نفــذ البحـــث لتقييـــــم الفعاليـــــــــــة التثبيطيــــــــــة لمستخلــــــــــص الأسيتــــــــــون، الإيتانـــــــول، الميتانــــــــــــول و الكلوروفـــــــــــورم لأشنـة Evernia prunastri وبتراكيز (25،50،75،100) ملغ/مل تجاه ثلاثة أنواع ممرضة من جنس Aspergillus هي: A. niger , , A. fumigatus A. flavus . تباينت فاعلية المستخلصات الأربعة، حيث أبدى كلا المستخلصين الأسيتوني و الميتانولي فعاليـــــــــة تثبيطيـــــــــــة ملحوظــــــــة تجاه الانواع الفطريــــــــــــة المدروســـــــــــة، إذ تزايـــــــدت الفاعليـــــــــة بازديـــــــــاد تراكيزهمـــــا، فعنــــــــــد التركــــــــــــيز (100)ملغ/مل ثبــــــــــــط النـــمـــــــــــو كلّياً لكـــــــــــــــلّ مــــــــــــــن A. niger , , A. fumigatus A. flavus ، بينما وصلت نسبـة التثبيــط لمستخلـص الإيتانول إلى (94.11، 78.82، 87.05)% على التوالي عند التركيز ذاته، أما بالنسبة لمستخلص الكلوروفورم فكان الأقل تأثيراً، حتّى عند التركيز (100) ملغ/مل، حيث بلغت نسبة التثبيــــــــــط 62.35) ،74.11، 68.23) % على التوالي مقارنة بالشاهد A. fumigatus.اعتماداً على هذه النتائج يمكن الاستفادة من مستخلصات أشنة Evernia prunastri كمصادر حيوية طبيعية لمعالجة الإنتانات الفطرية مستقبلاً.The research was carried out to evaluate the inhibitory efficacy of acetone, ethanol, and chloroform of Evernia prunastri lichen with concentrations of (25, 50, 75, 100) mg/ml. against three pathogenic species of Aspergillus sp. Which are: A. flavus, A. fumigatus and A. niger . The efficacy varied among the four extracts, where both the acetonic and methanolic showed noticeable inhibitory efficacy against the fungal species under study. The efficacy increased of both extracts, at concentration (100) mg/ml growth of A. flavus, A. fumigatus and A. niger was completely inhibited, whereas the inhibiton percentage for ethanol extract reached (87.05, 78.82, 94.11)%, respectively at the same concentration. As for the chloroform extract, it was the least effective, where the percentage at (100) mg/ml concentration reached (68.23, 74.11, 62.35) %, respectively, compared to the control.Depending on these results, the extracts lichen of Evernia prunastri could be used as natural products to treat fungal infections in the future.